Application of Additive Manufacturing to the Digital Restoration of Archaeological Artifacts. (2015) - Zhang, Fangjin; Campbell, Robert I.; Graham, Ian J.
Abstract: This paper reports a substantial body of work that has been done in this area, which has been used to determine how Additive Manufacturing (AM) and subsequent processes should be optimally applied, and introduces a series of process maps that have been generated to guide future practical work with a combination of questionnaires and expert interviews for validating the process maps. The outputs from the research should prove to be valuable to anyone working in this field. The main contribution to knowledge is the characterisation of archaeological artefacts and the resultant process maps derived from this characterization.